The Design and Development of Sistem Pengurusan Data Pemulihan Khas (SPDPK) PPD Cameron Highlands - Mohd Rusli, Nur Liyana; Azman, Azmeera Asfarina; Awang, Hapini; Che Mohamed Arif, Ahmad Suki; Mansor, Nur Suhaili; Mohd Salim Lim, Nurulhuda; Ling, Koh Shiau (Multidisciplinary Applied Research and Innovation, 2023)
Managing the remedial education data is considered difficult when using the traditional method where teachers need to insert the data manually and submit it via email to PPD officers. Then, PPD officers need to check each of the data that need to analyze in the file list. It is time-consuming and can cause the data checked to be overlooked. Therefore, Sistem Pengurusan Data Pemulihan Khas (SPDPK) aims to provide an online desktop application that can help teachers and PPD Cameron Highlands (PPDCH) officers save time in managing remedial education data. SPDPK can be used to insert remedial education data from schools across Cameron Highlands. The data that has been inserted will be displayed in the system dashboard to help PPDCH officers to analyze the data. Moreover, this system can also generate reports that can be customized according to the needs of PPDCH officers such as displaying the number of students based on race, school, and others. The design and development of the system followed the waterfall methodology. Firstly, the function requirement was gathered through the interview with the PPDCH officers and later was analyzed. After that, the SPDPK prototype has been developed based on the gathered requirements and a usability evaluation was conducted to evaluate this system. The result of the evaluation has shown that SPDPK is very useful and easy to use. Most of the respondents also stated they were satisfied with the SPDPK. The implementation of SPDPK could improve the traditional method to manage remedial education data more efficiently and conveniently.